Developing Instructional Materials for Nursing Students in Toraja South Sulawesi, Indonesia - Nehru P. Pongsapan (Teaching English as a Foreign Language Overseas Journal, 2015)
Need Analysis is very important before developing instructional materials for ESP. This research is aim 1) To explore the learning needs of English speaking skills for the nursing students. 2) To investigate the language needs of English speaking skills for the nursing students And 3) To develop an instructional material to meet the needs of English speaking skills for the nursing students in Toraja based on ADDIEstages.This research worked out Research and Development (R & D) with ADDIE (analysis-design-develop-implement-evaluate) approach. In analysis, the students’ needs obtained by employed questionnaires of 60 nursing students and 5 lecturers in Toraja, Indonesia and 14 nurses who have worked in hospital for English speaking community. Design and develop instructional material for nursing students based on Need Analysis. Instructional material developed by involving experts and the small group students at another Nursing Collage by using checklist and analyzed in quantitative method.The result shown that 1) learning needs cover language skills, and learning preferences in terms of activities and method. In language skills, writing, listeningspeaking and writing are recognized to be more suitable skills. In learning preferences; working in out of the class work or interaction with native speaker, demonstration or debate, and working large group work are needed in learning English than others. 2) language needs deal with language the important of English and English in the workplace. The important of English; for study and looking for the job are more preferred than others. English for workplace covers the situation in hospital where English used commonly. It is stated that situation such as giving advice, explaining laboratory test, and administering medication commonly use English. 3) English material developed based on needs analysis throughout ADDIE stage.